ANALISIS KEBUTUHAN AIR BERSIH DI DESA BATU MEKAR KECAMATAN LINGSAR PDAM LOMBOK BARAT - APRIANUS RIKO; BAGUS WIDHI DHARMA S.; KUSMIANTI KUSMIANTI (LPPM PSDKU Kampus Mataram UNMAS Denpasar, 2021)
The provision of clean water is currently a problem in PDAM services in West Lombok Regency. The need for clean water every year is increasing while the availability of clean water is limited, due to water loss. In order not to lose large enough need to emphasize water loss and water usage savings in anticipation of water shortages then it is necessary to find raw water sources again.This study aims to uncover: (1) how the condition of service is general in Batu Mekar Village (2) whether the water discharge available today is sufficient in Batu Mekar Village until 2025, (3) how much water needs of Batu Mekar Village customers.This type of research is a descriptive study to know the need of clean water in the Batu Mekar village area.The results of the study showed that the need for clean water in the Batu Mekar village area of public service amounted to 79,770 L/det, water discharge available in 2025 amounted to 565.29 L/det, total water needs in 2025 amounted to 553.54 L/det.